Ischemia modified albumin levels cannot predict stress induced ischemia shown by myocardial perfusion scintigraphy - Koc, Z. P.; Erkilic, M.; Basarici, I.; Deger, N.; Ozdem, S.; Saka, O. (Elsevier Doyma Sl, 2012)
Purpose: Ischemia modified albumin (IMA) is a new marker of ischemia which is used in especially emergency room. Aim of this study is showing the association of IMA with stress induced ischemia on Tc-99m 2-methoxyisobutyl-nitrate (MIBI) myocardial perfusion scintigraphy (MPS). Methods: 56 patients (23 F, 33 M; 56.04 +/- 8.45 years old) were included in our study. Stress-rest two days protocol Tc-99m MIBI MPS single photon emission tomography (SPECT) was performed to all patients. IMA levels from the blood samples which were taken before and after the treadmill test were measured. Thirty patients additionally underwent coronary angiography. Results: The difference of IMA levels of ischemia between positive and negative groups was not statistically significant. Also, there was not statistically significant difference between IMA levels of patients who have narrowing in the coronary arteries and not. Conclusion: Although IMA is an important marker of ischemia, probably because of other ischemic process during stress; it cannot reflect stress induced ischemic changes on MPS. (C) 2012 Elsevier Espana, S.L. and SEMNIM. All rights reserved.
Keywords: Myocardial ischemia; Myocardial perfusion imaging; Ischemia modified albumin; Tc-99m 2-methoxyisobutyl-nitrate; Scintigraphy